2022
DOI: 10.1590/0102-311xpt239521
|View full text |Cite
|
Sign up to set email alerts
|

Validade do instrumento para triagem de domicílios em risco de insegurança alimentar em diversos estratos da população brasileira

Abstract: A ausência de instrumentos de triagem de risco para insegurança alimentar compromete a capacidade de avaliar, monitorar e ofertar assistência imediata a pessoas em situação de fome, especialmente durante emergências, como a crise da COVID-19. Assim, o objetivo deste estudo foi testar a validade do instrumento de Triagem para Risco de Insegurança Alimentar (TRIA), em diversos estratos da população brasileira. A TRIA é composta pelas questões 2 e 4 da Escala Brasileira de Insegurança Alimentar (EBIA), validada, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 8 publications
1
4
0
6
Order By: Relevance
“…Finally, the positive responses to each of the BFIS questions showed that concern with food (53.7%) was one of the items that had one of the highest frequencies of FNI (65.7%), while the frequency of items related to food running out before having money to buy more and members only eating some of the food they had left because money ran out (26.2%) was very close to the prevalence of M-SFNI. These results are similar to those of previous studies in which BFIS questions were considered as a proxy for FNI and its severity 30 , 31 . It is important to note that FNS can be assessed based on isolated BFIS questions, since even a single positive response on the scale classifies the family as FNI.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, the positive responses to each of the BFIS questions showed that concern with food (53.7%) was one of the items that had one of the highest frequencies of FNI (65.7%), while the frequency of items related to food running out before having money to buy more and members only eating some of the food they had left because money ran out (26.2%) was very close to the prevalence of M-SFNI. These results are similar to those of previous studies in which BFIS questions were considered as a proxy for FNI and its severity 30 , 31 . It is important to note that FNS can be assessed based on isolated BFIS questions, since even a single positive response on the scale classifies the family as FNI.…”
Section: Discussionsupporting
confidence: 91%
“…The order of the BFIS questions, from mild to more severe situations, may explain the fact that the first item (concern with lack of food) is the one that best represents FNS 30 . In turn, the different FNI levels may be represented by aspects related to deprivations in the quantity and quality of food, and not with the concern with the lack of food 30 , 31 . In this sense, a recent study showed that the use of items 2 and 4 of the BFIS as parameters for differentiating FNI levels is useful 31 , providing credibility to our results regarding the similarity of the prevalence of M-SFNI and the frequency of positive response to these aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, a TRIA apresenta grande potencial na melhoria da governança da SAN, isso porque é um instrumento capaz de facilitar o monitoramento, o planejamento e a implementação de programas e políticas públicas coerentes e coordenadas de SAN, contribuir com a transparência e a responsabilidade das instituições na garantia do Direito Humano à Alimentação e a Nutrição Adequada (DHANA), e subsidiar a tomada de decisões para a alocação equitativa de recursos. O monitoramento sistemático da IA em nível local por meio da TRIA fornece à sociedade e aos tomadores de decisão dados fundamentais para a análise situacional e compreensão da magnitude do problema, demonstrando a capacidade da TRIA como instrumento de governança local (Carvalho et al, 2022).…”
Section: Teorizaçãounclassified
“…Por ser de rápida aplicação e fácil interpretação, a utilização da TRIA pode ocorrer como parte da rotina dos serviços 9 pronta tomada de decisão a partir da identificação de famílias em risco de IA e com possível experiência de fome, garantindo o direito à saúde e à alimentação adequada e saudável (Carvalho et al, 2022).…”
Section: Teorizaçãounclassified
“…Nesse panorama foi proposto medidas de segurança para a preservação da vida, uma destas foi o isolamento social, em que a maioria das atividades econômicas foram suspensas, permanecendo apenas as que eram consideradas essenciais, como mercados, hospitais, serviços de segurança pública. Devido a isto a taxa de desemprego cresce a cada dia chegando à marca de 10,1 milhões de desempregados no segundo trimestre de 2022 (ALPINO et al, 2020;IBGE.,2022;GUILHERME;CARVALHO;TABAI., 2021).…”
Section: Introductionunclassified